Participatory Land Use Planning in Natural Hazard’s Fragile Context: A Case Study of Kalam, Pakistan - Muhammad Jawed Iqbal; Ismail Khan; Muhammad Bilal Khurshed; Sadaf Saleem (European Scientific Journal, ESJ, 2016)
Land use planning is an integrated and multi-disciplinary approach towards using available land in a more appropriate way. This approach is contributing towards the sustainability of available resources, mitigating environmental degradation, better physical infrastructure, and mitigating natural disasters. The unplanned built up and inappropriate practices by human beings have led to the depletion of natural resources and an increase in vulnerability of the communities to natural disasters. Some factors which include lack of planning, rapid increase in population, and poor physical infrastructure further aggravate the situation. In such situations, there is a dire need to conduct surveys and equip the local communities with a knowledge and awareness of land use planning. This research is part of the project titled “Building Resilience through Community Disaster Risk Reduction” funded by Diakonie Katastrophenhilfe (DKH). This research presents the findings of the participatory land use planning exercise conducted in five villages of Kalam in Pakistan.